Electrician's calculations manual - Fowler, Nick. (New York : McGraw-Hill, 2012)
'THE ULTIMATE ON-THE-JOB COMPANION--FULLY UPDATEDThoroughly revised to reflect the 2011 National Electrical Code (NEC) and the latest industry advances, Electrician's Calculations Manual, Second Edition gives you quick access to the basic calculations needed for any given job. The book also serves as an ideal review for license preparation. End-of-chapter questions plus an end-of-book final test help reinforce the material covered. Written by a Master Electrician with more than 40 years of experience, this practical guide helps you: Find answers for both AC and DC circuits Solve problems related to motor circuits and transformers Calculate single-dwelling and multifamily loads Accurately figure requirements for commercial jobs Perform conduit-bending math Handle service entrance problems Understand the math behind electrical solutions And much more'--
'This handy book is the perfect go-to toolbox companion for quick access to the formulas and examples that electricians need to solve on-the-job problems'--
Keywords: Electrical engineering -- Problems, exercises, etc; Electrical engineering -- Mathematics -- Handbooks, manuals, etc; Mathematics -- Formulae -- Handbooks, manuals, etc